ANALISIS STRATEGI PROMOSI GLOBAL FORMULA ONE OLEH LIBERTY MEDIA (2017-2025) - Rafly, Rafael; Setyobudi, Bezaleel Yuvens; Rasyidah, Resa (POLITEKNIK LP3I JAKARTA, 2026)
This study analyzes Liberty Media's international marketing strategy for Formula One (F1) using Kotler's 7T Framework (Product, Service, Incentives, Brand, Price, Communication, Distribution), which successfully recovered F1 post-COVID-19. Under Liberty Media's ownership since 2017, F1 fundamentally transformed from an elite racing spectacle focused on technical aspects into a global media and entertainment property, successfully turning an operational loss of USD 386 million in 2020 into record revenue growth during the 2021–2024 period. Adopting a descriptive qualitative method with a case study approach and literature review technique, this research focuses on the implementation of Liberty Media's strategy from 2017 to 2025. The findings demonstrate a transformative success rooted in redefining F1's value proposition, which now centers on human drama narration (Drive to Survive) and fan proximity (F1 Unlocked), alongside strong brand differentiation (LVMH partnership). The synchronization of this 7T framework is realized through Product innovations such as the Sprint Race format and the Direct-to-Consumer (DTC) service F1 TV Pro; enhanced B2B Service through the Paddock Club; the free Incentives program